Evaluation of toxic effects of chemotherapy in lung malignancies on cerebral white matter using diffusion tensor imaging - Aydin Sinem; Demir Tarik; Turk Haci Mehmet; Cesme Dilek Hacer; Aliyev Altay; Ali Gultekin Mehmet; Fatih Yilmaz Temel; Alkan Alpay (Radiology and Oncology, 2022)
Non-small cell lung cancer (NSCLC) is a leading cause of morbidity and mortality. Carboplatin and cisplatin based regimens are used in the treatment of NSCLC. The aim of the study was to find out whether there is a difference in white matter (WM) changes between two platinum-based chemotherapy agents using diffusion tensor imaging (DTI).